What are the Care Needs of Families Experiencing Cardiac Arrest Care? A Survivor and Family-Performed Systematic Review and Qualitative Meta-Synthesis Protocol. (11th October 2021) - Douma, Matthew J.; Graham, Timothy A. D.; Bone, Allison; Ali, Samina; Dennett, Liz; Brindley, Peter G.; Kroll, Thilo; Frazer, Kate
Background: Sudden cardiac arrest is a leading cause of death. Family members can be deeply impacted by sudden loss or uncertainty about survivor outcomes. The objective of this systematic review will be to identify, appraise, and meta-synthesize qualitative evidence regarding family care-needs when experiencing cardiac arrest.Methods: This systematic review of qualitative studies and meta-synthesis will be conducted by multidisciplinary researchers in partnership with patient and family partners who have lived-experience of cardiac arrest. We will search MEDLINE, Embase, CINAHL, Theses and Dissertations Global, SocIndex, Scopus, Web of Science, PsycINFO, and Google Scholar. We will include qualitative research describing the experience and care needs of family members. We will also search reference lists, conduct forward citation searches, and contact content experts. We will assess the methodological quality of included studies using the Critical Appraisal Skills Programme tool. Two team members will independently review studies, extract data, and assess methodological quality. Disagreements will be resolved by consensus. We will use thematic framework analysis to analyze and synthesize narrative data, after which the review team and stakeholders discuss the findings and make any necessary changes. Our thematic synthesis will follow three steps: (i) initial coding and grouping of codes, (ii) formation of descriptive themes, and (iii) transcending the data to form novel insights and theories (analytical themes). The review will be reported in accordance with the ENTREQ and GRIPP2 guidelines. We will apply the Confidence in the Evidence from Reviews of Qualitative (CERQual) research to assess the robustness of our findings.Review Registration: This protocol has been registered with the International Prospective Register of Systematic Reviews (PROSPERO), registration number CRD42021236431 and Open Science Frameworkhttps://osf.io/fxp5g .